К.АЛЛАМБЕРГЕНОВТЫҢ «ҚУСЛАР ҚАЙТҚАН КҮН» ПОВЕСТИНДЕ ҚАҲАРМАН ПСИХОЛОГИЯСЫ ҲӘМ ТӘБИЯТ БИРЛИГИ МӘСЕЛЕСИ - Сагидуллаева, З.Б. (FAN va JAMIYAT, 2017)
The article is devoted to the study of features of psychologism in works of fiction. The theoretical aspect of an issue of ratio of the description of characters psychology with images of a picture of the natureis is revealed on the basis of K.Allambergenov's story «The Day when birds have flown away». At disclosure of psychology of characters the writer reaches the display of evolution of their characters. The author of the article pays attention to the use of elements of composition of the work of fiction as an artistic detail, conflict a landscape, an internal monologue, and also the skill of the writer as a story-teller.